Improvement of Learning Outcomes in IPAS for Fifth Grade Students at SDN 02 Bengkayang through the Flipped Classroom Model Supported by Google Sites - Antonius (Journal of Educational Learning and Innovation (ELIa), 2024)
This study aims to improve students' learning outcomes in Natural and Social Sciences (IPAS) at SDN 02 Bengkayang through the implementation of the flipped classroom model assisted by Google Sites. The research employs a classroom action research (CAR) approach conducted in two cycles, involving 34 fifth-grade students as the research subjects. Each cycle consists of planning, action implementation, observation, and reflection stages. Data were collected through learning outcome tests, observation sheets, and student response questionnaires, and then analyzed using both quantitative and qualitative methods. The results showed a significant improvement in students' learning outcomes following the implementation of the flipped classroom model. The percentage of mastery learning increased from 10.55% in the pre-test to 85.29% by the end of the second cycle. Additionally, students' responses to this learning model were very positive, with increased motivation, interest, and active participation in the learning process. Students also reported that the use of digital media like Google Sites helped them better understand the learning material. In conclusion, the flipped classroom model assisted by Google Sites proved to be effective in improving students' learning outcomes in the IPAS subject.